How citizenship norms predict participation in different political activities. (1st September 2020) - Reichert, Frank
ABSTRACT: How young people become active citizens to sustain democracy is a crucial question for a modern democracy like Australia to pose in a context of youth political disillusionment with politics. The present research investigates this question in the context of young Australian adults' norms of citizenship and intended political participation. The results show that encouraging young people to engage in decision-making processes in school or the community may cultivate active democrats, while law-abidingness works as a moderator of other citizenship norms. It remains a major challenge for democracies to promote engaged citizenship norms, prepare young people to be interested in civic issues, and facilitate skills that make politically self-efficacious young citizens.